2015
DOI: 10.29309/tpmj/2015.22.02.1367
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection

Abstract: Wound infection can be defined as invasion of organisms through tissuesfollowing a breakdown of local and systemic host defenses. The basic principles of wound careand antisepsis introduced during the past century improved surgery dramatically. Objective:Evaluation of causative organisms which evolved in the surgical site infection (elective abdominalsurgery) at surgical unit of Liaquat university hospital Jamshoro. Subjects & Methods: Thisprospective observational study was contains 103 patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Several studies conducted in Pakistan to find out the most common pathogen involved in SSI. Bashir et al, reported in their studies that E. coli found in 33.33% cases followed next in frequency by Staphylococcus aureus and Klebsiella in 20%, Proteus in 13.33%, Pseudomonas in 6.66% cases [41]. While Bibi et al, also reported E. coli (33.8%) as a most common pathogen followed by Pseudomonas aeruginosa (16.9%) and Staphylococcus aureus (15.5%) [42].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted in Pakistan to find out the most common pathogen involved in SSI. Bashir et al, reported in their studies that E. coli found in 33.33% cases followed next in frequency by Staphylococcus aureus and Klebsiella in 20%, Proteus in 13.33%, Pseudomonas in 6.66% cases [41]. While Bibi et al, also reported E. coli (33.8%) as a most common pathogen followed by Pseudomonas aeruginosa (16.9%) and Staphylococcus aureus (15.5%) [42].…”
Section: Discussionmentioning
confidence: 99%
“…5 In a study examining the pathogens commonly responsible for the formation of SSIs, 26.16% E.coli, 20% S. aureus, and K. pneumonia, 13.33% Proteus and 6.66% Pseudomonas were found. 6 Another study reported that the infectious agents were 26.16% E.coli, 22.53% Acinetobacter, 14.63% Staphylococcus, 11.78% Enterococcus, 8.16% Klebsiella, 7.64% Pseudomonas, 1.68% Candida, 1.42% Proteus and 2.59% other microorganisms. 7 In the study of Lakoh et al, 49 isolates belonging to 14 different bacteria were detected, including 41 gram-negative (83.7%) and 8 gram-positive (16.3%) isolates.…”
Section: Introductionmentioning
confidence: 99%